Gonadal development and intersex condition of marbled lungfish, Protopterus aethiopicus (Heckel, 1851), in contaminated sites in Lake Victoria, Uganda. Issue 4 (1st October 2020) - Badamasi, Inuwa; Odong, Robinson; Masembe, Charles
Abstract : The first evidence of the impact of environmental contamination on populations of Protopterus aethiopicus (Heckel, 1851) in terms of body indices, cellular development (histology) and intersex condition in Lake Victoria, Uganda is provided. Specimens were obtained from the more polluted swampy areas receiving wastes from residential and industrial settings (Ggaba, n = 11; Port Bell, n = 10; and Jinja, n = 7), and rural, less polluted areas (Bukakata, n = 3; Kasensero, n = 4; and Bale, n = 2), and gonadosomatic indices, growth condition factor and the morphometric body characteristics were determined. Fish specimens in less polluted sites had better condition and shapes, regardless of sex, compared with those in more polluted sites of the lake. Most lungfish collected had a total length of 45–55 cm. Irrespective of sex of fish and level of pollution at collection sites, samples ( n = 26) collected inshore (1 063.42 g ± 109.32 SE) were heavier than those collected ( n = 11) offshore (680.09 g ± 108.85 SE), F (1, 35) = 6.288, p = 0.019. Mean values of gonadosomatic indices were significantly higher in less polluted sites, compared with chemically contaminated urban sites ( F (5, 31) = 2.783, p = 0.034), suggesting better growth performance in the former. Spermatogenic cell development progressed as spermatogonia, spermatocytes, spermatids and spermatozoa among males. For oogenic cells, development was through chromatin nucleolar, perinucleolar, cortical alveolar, early vitellogenic and late vitellogenic oocytes. Histological examinations revealed group asynchronous gonadal development and intersex condition among P. aethiopicus populations in Lake Victoria.